2011
DOI: 10.1088/0022-3727/44/23/235201
|View full text |Cite
|
Sign up to set email alerts
|

Performance characterization of a helicon double layer thruster using direct thrust measurements

Abstract: Abstract. The performance of a Helicon Double Layer Thruster (HDLT) has been characterised using a pendulum type thrust stand and retarding field energy analyser. Data recorded for a fixed propellant flow rate of 16 sccm of krypton and fixed magnetic field topology show that the thrust generated increases linearly with increasing radio frequency input power over a range of 250 W to 650 W. Over the power range investigated thrust levels of approximately 1 to 2.8 mN were achieved. A maximum effective specific im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 19 publications
5
86
0
Order By: Relevance
“…1,2,4,6 While prolific studies of the fundamental physics in such systems have been done, detailed experimental measurements of the thrust of such devices are only now beginning to be performed. 7,8 These thrust measurements are vital, as they allow almost all other electric propulsion figures of merit to be determined, 9 and thus, the performance of such systems to be assessed.Fruchtman has provided much of the theoretical groundwork for such plasma thrusters and has performed a number of detailed analyses in collisionless 10 and collisional regimes, 11 as well as investigating the effects of neutral depletion 10,11 and magnetic expansion. 12 In particular, in the absence of a magnetic field, the thrust has been predicted to be strongly linked to the maximum upstream electron pressure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4,6 While prolific studies of the fundamental physics in such systems have been done, detailed experimental measurements of the thrust of such devices are only now beginning to be performed. 7,8 These thrust measurements are vital, as they allow almost all other electric propulsion figures of merit to be determined, 9 and thus, the performance of such systems to be assessed.Fruchtman has provided much of the theoretical groundwork for such plasma thrusters and has performed a number of detailed analyses in collisionless 10 and collisional regimes, 11 as well as investigating the effects of neutral depletion 10,11 and magnetic expansion. 12 In particular, in the absence of a magnetic field, the thrust has been predicted to be strongly linked to the maximum upstream electron pressure.…”
mentioning
confidence: 99%
“…1,2,4,6 While prolific studies of the fundamental physics in such systems have been done, detailed experimental measurements of the thrust of such devices are only now beginning to be performed. 7,8 These thrust measurements are vital, as they allow almost all other electric propulsion figures of merit to be determined, 9 and thus, the performance of such systems to be assessed.…”
mentioning
confidence: 99%
“…(4) and Eq. (6), can be expressed as (8) where the first term of the right-hand side (rhs) is the Lorentz force due to the net azimuthal current j j i j e and the radial magnetic field B r . The electron and ion azimuthal current can be obtained from Eq.…”
Section: Analytical Thrustmentioning
confidence: 99%
“…The direct measurement of the thrust imparted by helicon thrusters operated at about 1 kW is presently being performed and the first results have shown the thrust of about 2-3 mN for 1 kW rf power 6,8) . In these experiments, it is reported that the static electron pressure inside the source is converted into the ion dynamic momentum through a spontaneously formed double layer or an ambipolar electric field.…”
Section: Introductionmentioning
confidence: 99%
“…For example, on condition of th ermal shock of high and low temperature, various operations and measurements are completed in a va cuum. Within the parametric analysis and design of torsion thrust measurement, thrusters' size, weight, maxi mum thrust, the calibration convenience of system parameters and the time required in thrust measure ment process, are all needed to taken into consideration [3] . The torsion system parameters include damping ratio, vibration frequency, torsional stiffness and moment of inertia, etc., and parameters of measured thrusters are as follows: (1) Size and weight of thrusters.…”
Section: Introductionmentioning
confidence: 99%